Violence, monumentality and power: the Alexandrine conflict of 38 AD - Sena, Nicodemo Valim de (Romanitas - Revista de Estudos Grecolatinos, 2016)
This article aims to analyze the relationship between violence, monumentality and power in the formation and affirmation of the identity of Greeks, Egyptians and Jews. Therefore, we sought to understand through the work In Flaccum and Legatio ad Gaium by Philo of Alexandria, as some buildings of Alexandria (gym, theater and synagogue) were destroyed, appropriated and reinterpreted during the Conflict of 38 AD.